Analisis Resiko dalam Evaluasi Kebijakan Privasi dan Keamanan Data Hard pada Ruang Arsiparis di BAPENDASU Menggunakan Distribusi Poisson - Akhiriyah Ramadhani; Farica Luthfiyah; Rima Aprilia (Kampus Akademik Publiser, 2026)
The security of physical archives is essential for maintaining the confidentiality, integrity, and availability of information within government institutions. This study aims to analyze the risks associated with privacy policies and hard-copy data security in the archivist room of the Regional Revenue Agency of North Sumatra Province using the Poisson distribution approach. This research employed a descriptive quantitative approach with a case study method. Data were collected through observation, documentation, and literature review, and were analyzed by identifying physical, security, technological, internal, and external risk factors. The Poisson distribution was applied to estimate the probability of document loss or damage based on the average frequency of incidents within a specific period. The findings indicate that the probability of document loss or damage remains significant, highlighting the need to strengthen security controls through enhanced surveillance systems, access control implementation, staff capacity building, and archive digitization. The application of the Poisson distribution provides a probabilistic assessment of archive security risks and serves as a data-driven basis for developing more effective and adaptive archive security policies within the Regional Revenue Agency of North Sumatra Province.